Work Value and Occupational Hazard as Correlates of Organisational Citizenship Behaviour Among Employees of International Brewery Plc. Ilesa, Nigeria - Ayinde, Adeboye Titus; Oladoyinbo, A. A. (European Scientific Journal, ESJ, 2016)
The importance of organisational citizenship behaviour can never be over emphasised in organisation striving for competitive advantage. Thus, this study examined employees’ organisational citizenship behaviour in relation to factors such as perceived work value, occupational hazard and the combined influence of both factors on organisational citizenship behaviour among employees of International Brewery Plc, Ilesa, Osun State. This is with a view to determining factors that influence organisational citizenship behaviour among workers. Primary data were used for the study. The data were collected from the 269 respondents, which cut across eleven departments: Production, Distribution, Technical, Commercial, Research and Development, Security, Management Information, Quality Assurance, Human Resource, Personnel, Accounting and Audit and Financial department using stratified random sampling technique. Three standardized Psychological Scales were used in the study. These were the Work Value Facet of Personal Life Value Questionnaire (WVFPLV), Organisational Safety Climate Scale (OSCS), Organisational Citizenship Behaviour Checklist (OCB-C). Data collected were analyzed using the appropriate descriptive statistics and inferential statistics. Results showed a significant relationship between work value and organisational citizenship behaviour among employees of International Brewery Plc, Ilesa r (267)=0.350), P 0.05. The study concluded that work value has and occupational hazard jointly determined organisational citizenship behaviour.